SYMMETRY AND ASYMMETRY IN FORMS AND DECORATIVE FINISH OF MUSLIM GRAVESTONES OF THE 14th -15th CENTURIES IN THE VILLAGE OF KUBACHI - Mammaev, M M (History, Archeology and Ethnography of the Caucasus, 2017)
This article is sequel to the article published in the third issue of the Journal “Herald of the Institute of History, Archeology and Ethnography of the Dagestan Scientific Center of the Russian Academy of Sciences” in 2017 and it deals with the peculiarities of decorative finish of Muslim gravestones of the 14th -15th centuries in the village of Kubachi, partly in the village of Ashty, and now uninhabited villages of Dats’amazhe and Kalakoreish. This article, unlike the previous one, covers the issues related to the principles and methods used by stonecutters, calligraphers and ornamentalists in the decoration of the headstones. The analysis shows that bilateral symmetry was the guiding principle, which stonecutters used in decorative finish of the gravestones and of various architectural details as well. It is noted that the patterned and epigraphic compositions presented on the medieval headstones are based on the principle of free or relative symmetry, since there is no exact coincidence of the left and right sides of the figures. Along with the compositions with bilateral relative symmetries, there are the so-called mirror symmetries, in which the left and right sides are the same and coincide. These are mainly compositions of floral ornament. In medieval stone-cutting art of the village of Kubachi, mirror symmetry is most often found in heraldic compositions with images of paired, opposing animals, birds and fantastic creatures carved on various architectural details. The stonecutters adhered to the principle of relative (free) symmetry while making relief decorative Arabic inscriptions against the background of the floral ornament. The same inscription of the patterned and epigraphic band (border) in the upper part of many headstones is divided into two equal parts by a small ornamental medallion or braided ornament. But according to the figure (structure) these parts (right and left) are different. The stonecutters were to show the symmetry of the whole decoration of the headstones - the center and its sides. Among the architectural details there are also some decorative Arabic inscriptions executed in compliance with bilateral mirror symmetry. This symmetry is presented in the inscription (pseudo-inscription) on the archivolt of the window tympan of late 14th - early 15th centuries with the image of a horse rider, and on the archivolt of the window tympan with the image of a deer dropped down to the front legs. The author of the article presents the data on the relationship between Kubachi and the neighboring villages of Itsari, Shiri, Dats’amazhe in the development of the stone-cutting art and other types of decorative and applied art - wood carving, metalworking, carpet weaving, etc. in terms of similarity of compositional techniques and ornamental motives, performed in compliance with the principle of symmetry. The author analyzes similarities and differences in the decoration of the headstones at the medieval cemeteries of the village of Kubachi - “Bidaq huppe”, “Ts’itsila”, “Baqutsila”, “Dats’amazhe”, and also in the villages of Ashty and Kalakoreish. The modern ornamental art of Kubachi has inherited the rhythm, symmetry, balance, and proportionality peculiar to medieval ornamental compositions.